2007
DOI: 10.1038/oby.2007.206
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the SCD1 Gene: Associations With Body Fat Distribution and Insulin Sensitivity

Abstract: Objective: Obesity and insulin resistance are major risk factors for metabolic diseases and are influenced by lifestyle and genetics. The lipogenic enzyme, stearoyl-coenzyme Adesaturase (SCD), is related to obesity. Further, SCD1-deficent mice are protected against obesity and insulin resistance. We hypothesized that genetic polymorphisms in the SCD1 gene would be associated with obesity, insulin sensitivity, and estimated SCD activity in humans. Research Methods and Procedures:The study population was 1143 el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
70
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 25 publications
7
70
3
Order By: Relevance
“…For example, APOLD1 (apolipoprotein L domain containing 1), identified in HUVECs and EDG1 (sphingosine-1-phosphate receptor 1), identified in CBMCs, both regulate vascular function in mice and humans (Liu et al 2000;Regard et al 2004;Simonsen et al 2010;Gordon et al 2011). Even though no genes in placenta reached significance after multiple testing, polymorphisms in the genes ranked 1 and 2, HLA-B (major histocompatibility complex class 1B) and SCD (stearoyl-CoA desaturase), have been associated with low birth weight and metabolic disease, respectively, in humans (Warensjo et al 2007;Sampath and Ntambi 2008;Capittini et al 2009;Shin et al 2010). …”
Section: Identification Of Discordantly Methylated Genes Associated Wmentioning
confidence: 99%
“…For example, APOLD1 (apolipoprotein L domain containing 1), identified in HUVECs and EDG1 (sphingosine-1-phosphate receptor 1), identified in CBMCs, both regulate vascular function in mice and humans (Liu et al 2000;Regard et al 2004;Simonsen et al 2010;Gordon et al 2011). Even though no genes in placenta reached significance after multiple testing, polymorphisms in the genes ranked 1 and 2, HLA-B (major histocompatibility complex class 1B) and SCD (stearoyl-CoA desaturase), have been associated with low birth weight and metabolic disease, respectively, in humans (Warensjo et al 2007;Sampath and Ntambi 2008;Capittini et al 2009;Shin et al 2010). …”
Section: Identification Of Discordantly Methylated Genes Associated Wmentioning
confidence: 99%
“…83 However, recently eight single nucleotide polymorphisms of the human SCD1 gene were reported to be associated with obesity and obesity-related insulin resistance. 84 Other contradictory evidence emerged from a study with obese diabetic patients treated with rosiglitazone to counter their insulin resistance. In these patients, SCD1 mRNA levels were elevated instead of downregulated.…”
mentioning
confidence: 99%
“…Rodent and cell culture studies have suggested an important role of SCD1 in the pathogenesis of obesity (1,5 ), insulin resistance (1,5,6 ), diabetes mellitus (7 ), and atherosclerosis (8 -11 ) as well as inflammatory diseases (3,(12)(13)(14)(15)(16). Therefore, there has recently been considerable interest in the determination of SCD1 activity in human samples to elucidate the role of SCD1 for health and disease in clinical studies and interventions (3,4,(13)(14)(15)(16). Apart from elegant stable isotope techniques to directly determine SCD1 desaturation activity in vivo (13 ), the ratios of SCD1 product and precursor fatty acids (18:1n9/18:0 and 16:1n7/16:0) in various accessible tissues (adipose tissue, skeletal muscle) have been used as a surrogate of enzyme activity in studies of small human cohorts (3,14,17 ).…”
mentioning
confidence: 99%
“…Stearoyl-coenzyme A desaturase 1 (SCD1) 4 is a microsomal enzyme that catalyzes ⌬9 desaturation as the limiting step of monounsaturated fatty acid synthesis (1 ). The cellular activity of the short-lived enzyme SCD1 is highly regulated and determined by the amount of enzyme present in the cell.…”
mentioning
confidence: 99%
See 1 more Smart Citation